La comprensión de las otras mentes según la filosofía de la mente y del lenguaje de Wittgenstein - Mundaca Gonzáles, Dennis Emiterio (2022)
The present work is an attempt to recover Wittgensteinian ideas around the understanding of others. From the grammatical analysis of language and the analysis of the mental phenomena developed by Wittgenstein in some of his works, the aim is to clarify the meaning of the understanding of another mind. Using the concepts "language games" and "ways of life", we analyze the beliefs of others in relation to our own. These ideas lead us to understand that the meaning of comprehension in Wittgenstein's thought supposes aspects that go beyond an explanation or theorization of the behavior of others.